Effect of Traditional East Asian Medicinal herbal tea (HT002) on insomnia: a randomized controlled pilot study - Sujeong Mun; Siwoo Lee; Kihyun Park; Sang-Jae Lee; Byung-Hee Koh; Younghwa Baek (Integrative Medicine Research)
Background: Complementary and alternative medicine treatment for insomnia has been sought due to the possible adverse effects of conventional pharmacotherapies. We performed a preliminary evaluation of the feasibility of using, and of the effect of a herbal tea (HT002), based on Traditional East Asian Medicine, in mild-to-moderate insomnia. Methods: Patients (n = 40) with mild-to-moderate insomnia were randomized to the HT002 (n = 20) or waitlist (n = 20) groups. The HT002 group consumed HT002 twice daily for 4 weeks. Outcomes were assessed using the Insomnia Severity Scale (ISI), Pittsburgh Sleep Quality Index (PSQI), and 12-item Short Form Health Survey (SF-12) at baseline and after 4 and 8 weeks. Results: The ISI score differences from baseline at weeks 4 and 8 were significantly greater in the HT002 than that in the waitlist group (week 4: −4.0 ± 0.8 vs. −0.4 ± 0.8, p < 0.05; week 8: −4.8 ± 0.7 vs. −0.9 ± 0.7, p < 0.05). Changes in PSQI and SF-12 physical component scores in the HT002 group were significantly greater at weeks 4 and 8 (p < 0.05), while SF-12 mental component scores were only significantly larger at 4 weeks (p < 0.05). HT002 was well-tolerated, with only one (5.0%) dropout, and no significant mean liver and renal function test changes post-treatment. Conclusion: Our preliminary results suggest that a 4-week treatment with HT002 may reduce the severity of insomnia symptoms and improve the quality of life. Further studies devoid of the limitations of our protocol may provide stronger conclusions. Trial registration: Clinical Research Information Service (CRIS), KCT0001900. Keywords: Herbal medicine, Herbal tea, Insomnia, Randomized controlled trial